Correlation of aortic valve annular plane assessment by on‐table three‐dimensional rotational angiography and preprocedural computed tomography. Issue 7 (20th November 2022) - Tanner, Richard; Murphy, Sean; Malone, Ciara; McGorrian, Catherine; Sugrue, Declan; Barton, David; Byrne, Roger; Blake, Gavin; Margey, Ronan; Casserly, Ivan P.
Abstract: Objectives: To assess the correlation between the aortic valve annular plane (AVAP) obtained by preprocedural computed tomography (CT) with on‐table three‐dimensional rotational angiography (3DRA), in patients undergoing transcatheter aortic valve replacement (TAVR). Background: Accurate assessment of the AVAP is critical during TAVR procedures to enable optimal positioning and minimize complications. Most commonly, preprocedural CT has been used to determine the AVAP. However, this can differ from the actual AVAP obtained during the TAVR procedure. Methods: Consecutive TAVR patients at a single center undergoing both preprocedural CT and 3DRA were included in the study. The AVAP assessment by CT was performed using 3mensio software (Pie Medical Imaging). 3DRA assessment was performed using DynaCT (Siemens). Results: A total of 100 patients were included in the analysis. A difference of ≥5° and ≥10° in both the LAO/RAO and cranial/caudal components of the AVAP projection angle as assessed by CT and 3DRA was recorded in 39% and 10% of patients, respectively. The concordance correlation coefficient for the LAO/RAO and cranial/caudal implantation angles was 0.519 (95% CI: 0.377–0.661) and 0.558 (95% CI: 0.432–0.684), respectively. Conclusion: Correlation between preprocedural CT and on‐table 3DRA in the prediction of the actual AVAP at the time of TAVR implantation is moderate.